Benthic macroinvertebrates of a tropical lake: Lake Caçó, MA, Brazil - Lucca,JV. (2010)
Benthic communities are highly relevant in the study of aquatic ecosystems, both for their role in the functioning of the ecosystem and also as markers or indicators of paleo-conditions. Their distribution, as in other communities, is conditioned by abiotic and biotic factors and to their interactions, which determine the structure of the community that is established. The aim of this study was to determine the taxonomic composition, abundance and spatial distribution of the benthic community, by collecting at 20 sampling sites in Caçó Lake (State of Maranhão, Brazil). Seasonal variation in these community parameters was analysed and related to the seasonal displacement of the Intertropical Convergence Zone. The results indicated that changes occur in the taxa richness, diversity and density of the benthic species of this lake that are mainly related to seasonality. All those parameters were higher in the dry than in the rainy period. The family Chironomidae (Diptera, Insecta) was the most important component of the community, representing approximately 50% of the total benthic fauna of the lake. The identification of the Chironomidae currently occurring in Lake Caçó is relevant, even at the genus level, considering the fact that this group produces fossilizing remains and could perhaps be good paleolimnological and paleoclimatic tracers that could be used to make inferences on past lake and climate conditions.